Holter Monitoring of Small Breed Dogs with Advanced Myxomatous Mitral Valve Disease with and without a History of Syncope. (13th January 2014) - Rasmussen, C.E.; Falk, T.; Domanjko Petrič, A.; Schaldemose, M.; Zois, N.E.; Moesgaard, S.G.; Åblad, B.; Nilsen, H.Y.; Ljungvall, I.; Höglund, K.; Häggström, J.; Pedersen, H.D.; et al.
<x xml:space="preserve">Abstract</x> Background Syncope is a transient loss of consciousness occasionally occurring in dogs with advanced myxomatous mitral valve disease (MMVD). Objective (1) To study ECG changes during syncopal episodes in dogs with advanced MMVD and (2) to compare the occurrence of arrhythmias and changes in heart rate variability (HRV) between dogs with advanced MMVD with and without a history of syncope. Animals Forty‐three privately owned dogs (<15 kg) with advanced MMVD: 21 with and 22 without a history of syncope. Methods Prospective study with dogs recruited for an evaluation including history, physical examination, echocardiography, and arrhythmia and HRV analysis performed on 24‐hour Holter recordings. Results A syncopal episode was observed during Holter monitoring in 4 dogs: 3 dogs had sinus rhythm and 1 dog had sinus arrest followed by escape rhythm. An arrhythmia variable representing sinus arrhythmia was significantly lower in dogs with a history of syncope than in those without (P = .008). Eight of 26 HRV variables were significantly different between dogs with and without a history of syncope. Conclusions and Clinical Importance Compared with dogs without a history of syncope, dogs with advanced MMVD and a history of syncope did not have a higher occurrence of arrhythmias, but had less sinus arrhythmia, and had changes in HRV variables representing decreased overall HRV, decreased parasympathetic, and increased sympathetic modulation of heart rate.